A Bibliometric Analysis of Prominent Themes in Management Information Systems - Gür, Yunus Emre; Ayden, Cem (My University, 2023)
This study does a bibliometric analysis to identify important themes in the academic literature on Management Information Systems (MIS) and to investigate how these subjects have evolved over time. Vosviewer and R Studio were utilized as analytic tools. On July 6, 2023, a search for \"topic\" with the term \"Management Information Systems\" yielded 2585 items for the period 1970–2023 in this bibliometric analysis. This analysis uses the Web of Science database to find pertinent bibliometric research studies. Studies carried out between 1970 and 2023 (till June) were included in the study's search on the Web of Science database. The findings highlight some important main ideas and sub-themes in the MIS discipline. Also looked at was how these motifs evolved and altered throughout time. This study offers a place to start when assessing broad trends in MIS research and pinpointing potential future difficulties. Researchers and practitioners can use this information to find and close gaps in the literature. As a result, the important topics and trends in the MIS literature are better understood thanks to this bibliometric research. The analyses also demonstrate how specific themes have changed over time and how these problems may serve as a basis for future study.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; İşletme